Investor Sentiment in Stock Market: A Case of Pakistan Super League in Pakistan Stock Exchange - FURQAN ULLAH; MUHAMMAD ASIF; MUHAMMAD ZAHID; FAIZA MEHREEN (Journal of Business & Tourism, 2021)
This study investigates whether sentiments play any role while investors make financial decisions which results in the stock returns. The paper analyzes the major two sports events (2016-2017) of Pakistan Super League (PSL). The study utilizes the stock market data from Pakistan Stock Exchange (PSX)-100 index for the period of two financial years starting from June 2015 to July 2017. PSL T20 data is collected from the official PSL website. The empirical results of the studyshow that PSL sports events are highly statistically significant and imply that the events trigger investor sentiments (optimistic and pessimistic behaviors) in the PSX.When the whole PSL games were played on United Arab Emirates (UAE) grounds in 2016, later on, which badly affected the investor moods and resulted in a negative abnormal return in PSX-100 index. While in case of PSL event in 2017, in which only final match of the event was held in Lahore, Pakistan and resulted in a positive abnormal return in PSX-100 index. The study provides implications for different authorities such as Pakistan Cricket Board (PCB), PSX and other development authorities in order to promote such activities for the overall economic and social benefits. While founding no previous studies concerning the subject in the Pakistani context, the Scholar selected the issue to conduct a research and make a considerable contribution for investors in Pakistan with respect to PSL events and its impact on PSX. Keywords: Investor Sentiments, Stock returns, behavioral finance, Pakistan Super League, Pakistan Stock Exchange